Psychological Needs and its Relationship with Electronic Bullying among High School Students in Nablus Governorate - Abu Helal, Yasmin Hasan (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to reveal the correlation between psychological needs and electronic bullying among the students of the higher basic stage in the schools of Nablus governorate. It also aimed to identify the level of prevalence of electronic bullying among the students of the higher basic stage, and to identify the extent to which variables (gender, place of residence, Grade level, economic level, and academic achievement) by predicting the level of electronic bullying among students in upper ‎ basic stage in Nablus governorate. To achieve these objectives, the descriptive associative method was applied. The questionnaire was used as a measuring tool After confirming their psychometric properties, the study sample consisted of (220) students (156) males and (64) females from governorate schools. The sample was selected according to random cluster method. The results of the study showed that the prevalence of cyber bullying was greater among tenth graders, followed by the ninth grade, followed by the eighth grade. the results also showed a statistically significant correlation between the following psychological needs (Satisfying the need for love and belonging, Satisfying the need for self-esteem, Satisfying the need for curiosity, Satisfying the need for security) and electronic bullying, the results also showed that variables: gender and grade and the academic achievement were able to predict electronic bullying according to the following ratios: gender )9.3%( for males, Grade )2.3%( The higher the grade the more bullying electronic, academic ‎achievement )1.2%( The less academic achievement the more electronic bullying among students in upper ‎ basic stage.